Posttraumatic stress disorder after cancer diagnosis in adults: A meta‐analysis. Issue 4 (28th July 2016) - Swartzman, Samantha; Booth, Josephine N.; Munro, Alastair; Sani, Fabio
Abstract : Background: Since the introduction of serious illness as a potential traumatic stressor in the fourth version of the Diagnostic and Statistical Manual of Mental Disorders (DSM‐IV), research on the prevalence and predictors of posttraumatic stress disorder (PTSD) after cancer diagnosis has proliferated. Studies have reported widely varying estimates of the number of people with PTSD after cancer. The aim of this review is to synthesize quantitative data from studies reporting the proportion of people with PTSD among groups of cancer survivors. Methods: We undertook a diversified literature search strategy and identified 120 samples from 110 sources reporting a proportion of cancer survivors with PTSD. Of these, 11 studies, containing 12 samples, reported estimates of PTSD in cancer survivors compared to matched controls. Results: A random effects meta‐analysis estimated the odds ratio as 1.66 (95% confidence interval (CI): 1.09–2.53) for PTSD in cancer survivors compared to controls, although some of this apparent increase may have arisen from publication bias. Factors influencing the reported proportion of a postcancer sample with PTSD included measurement type (clinical interview vs. self‐report instrument), type of cancer, type of treatment, geographic region, whether the term "posttraumatic stress" was in the title or abstract, prior trauma, age, and time since diagnosis. Conclusions: PTSD, diagnosed according to DSM‐IV criteria, is more common in survivors of cancer than it is in the general population. Estimates of the occurrence of PTSD in patients with a history of cancer depend upon clinical and demographic factors, as well as upon study design.